Changing Population Characteristics in Parsa - Yadav, Keshav Kumar (Academic Voices: A Multidisciplinary Journal, 2011)
The populaton of Nepal has been growing steadily for the last several decades. The rapidly growing population, at alarming state in Parsa (Nepal), is an indicator of the change in population status. This paper explores the changing population characteristics of Parsa district in terms of size, growth rate, density, distribution, composition, dependency ratio, marriage age, literacy status, religion, caste/ethnicity as well as the major mother tongue which is vital for local planning. It is based on the secondary data collected from different censuses of Nepal. Keywords Population distribution, density, age dependency, sex ratio, literacy status DOI: http://dx.doi.org/10.3126/av.v1i0.5305 Academic Voices 2011; 1: 26-30